(untitled) (The Pakistan Development Review, 2007)
There are major developments taking place around the globe affecting Pakistan and the region. Pakistan is dealing with various social, cultural and security issues on its internal side. On the other hand, the dynamics of globalisation are also having an impact offering both challenges and opportunities. Taking into consideration the need for an expert discussion on such issues facing Pakistan, the Islamabad Policy Research Institute held a seminar on “Pakistan and Changing Scenario: Regional and Global”. This book contains the research presented in this seminar and is divided into six chapters.